The Green Mosques: Catalysts for Environmental Stewardship and Sustainable Development in Muslim Communities - Abdul, Saboor; Zainab, Manzoor; Rashid, Shabir Abbasi (Universitas Ahmad Dahlan, 2024)
This paper emphasizes the up-and-coming place of mosques in promoting environmental care and sustainable development among Muslim communities. In so doing, it places mosques at the forefront of one of the potentially transformative agents of change with respect to climate challenges by aligning Islamic teachings on stewardship with modern ecological practices. To relieve the environmental burden, it aims to show how mosques can be implicated in the greenest technologies, such as renewable energies, water conservation systems, solid waste management, and architectural design. Through desk research and case studies of mosques in Indonesia, Malaysia, and Morocco, the research underlines the initiatives that have reduced energy consumption, optimized water use, and fostered community involvement. In this regard, the Morocco Green Mosque Program has been able to reduce energy consumption by as much as solar panel installations do. At the same time, mosques in Indonesia have implemented rainwater harvesting and greywater recycling. Additionally, mosques serve as community centers for environmental education, wherein religious teachings have engaged more than 70% of congregants in sustainability programs. Funding and long-term maintenance remain significant challenges, which justifies strong policy support and alignment with the Environmental, social, and governance (ESG) framework. Moreover, mosques can be pivotal in educating the younger generation on climate awareness, shaping them to become future advocates for environmental protection. This study indicates the potential of mosques for fulfilling religious duties to enable meaningful contributions toward global climate action and the SDGs.